X to Bluesky platform migration: Governance and community - Oeldorf-Hirsch, Anne (AoIR Selected Papers of Internet Research, 2026)
The results of the 2024 U.S. Presidential election led millions of X (Twitter) users to move to other platforms, following Musk’s support for president-elect Trump. Most users fled to Bluesky, driven by a desire for a community space with greater transparency, stronger moderation policies, and less hate speech. While online platform migrations happen regularly, they are not always this acute or this large. Therefore, this migration presents a unique case study for building online platform migration theory. This project investigates the X to Bluesky migration from a communication media lens. It is hypothesized (per media system dependency theory) that the social turmoil of the recent US Presidential election should lead to greater dependency on X, which would normally lead to greater platform adoption. However, it is theorized that given platform communication violations (per interpersonal expectancy violation theory), users migrated to other platforms (e.g., Bluesky) given a variety of “push” and “pull” factors (per migration theory), and moderated by the critical mass of their network. The present study will present survey results of former X/Twitter users (N = 200) who are now on Bluesky, about their reasons for migrating, to test these hypotheses. The project has received funding and is currently under university ethics board review. Data collection and analysis will be complete by the AoIR conference in October 2025.